A Case Report of Administering Rational Emotive Behavioral Therapy in Gambling Disorder - Ekici, Esengül; Yığman, Fatih; Güriz, Olga (Addicta: The Turkish Journal on Addictions, 2022)
A case study of a 37-year-old man who was diagnosed with gambling disorder with constant and uncontrollable Foreign Exchange Market investment and was administered rational emotive behavioral therapy in his treatment is presented in this article. This case was followed up for approximately 1 year, and 24 sessions of therapy were administered to the patient. In addition to the pharmacotherapy chosen according to the comorbidity that is commonly found in patients with gambling disorder, a heterogeneous disorder, the vitality of selecting the individual psychotherapy method according to the predisposing factors for the individual has been discussed on a case-by-case basis.